PERSEPSI DAN ASPIRASI MASYARAKAT TERHADAP PENGEMBANGAN OBJEK WISATA BUKIT BIRAH KECAMATAN PANYIPATAN KABUPATEN TANAH LAUT - Stephany Turnip; Fonny Rianawati; Khairun Nisa (Universitas Lambung Mangkurat, 2020)
Bukit Birah is located in Kandangan Lama, Panyipatan sub district, Tanah Laut regency has a height of 275 mdpl. Bukit Birah offers beautiful panorama, we can feel the atmosphere of villages, enjoy the view of the ocean and the hill. So that, the climber can enjoy the beauty of sunset and sunrise. Bukit Birah devolpment has an effort to become a tourist destination, which can be determined by the perception or views of the community about what can be seen from a tourist area. The purpose of this study is to examine the perceptions and aspirations of the tourists to develop the object of Bukit Birah in the village of Kandangan Lama. Respondents in this study were tourist and residents of RT 06, RT 04 and RT 01. Interview was conducted by asking tourist and residents by questionnaires. The results of this study indicate that the perception of tourist to the landscape attraction that is 63,4 % states strongly agree with the beauty. The aspiration of tourist (73.1%) stated that there was a need for promotion of the existence of tourism objects for the development of Bukit Birah. The residents stated that the existence of Bukit Birah tourism objects could increase the income of the residents by 53,2 %. The residents participated directly or indirectly in tourism activities on Bukit Birah. Keywords: Perceptions; Aspiration; Participation; Bukit Birah